Thailand : Financial Sector Assessment Program-Technical Note-Risk Assessment. (IMF Staff Country Reports; Country Report ;, 2019)
This technical note on the risk assessment for Thailand discusses that the Thai banking system shows a substantial resilience to severe shocks. The solvency stress tests indicate that the largest banks can withstand an adverse scenario broadly as severe as the Asian financial crisis. While three banks would deplete their capital conservation buffer (CCB) under the adverse scenario, recapitalization needs would be minimal. A battery of complementary sensitivity stress tests, which allows to cover in more detail certain risk factors, also confirmed the overall picture of a resilient baking system: no particular vulnerability emerged from the analysis of the bond portfolio to an increase in government and corporate spreads, exposure to foreign exchange risk, and concentration risk in the loan portfolio, with the possible exception of one entity with a particular concentration on single-name exposures. The liquidity stress test on investment funds (IFs) showed that they would be able to withstand a severe redemption shock and its impact on the banks and the bond market would be limited.